Factors Influencing Vegan Cosmetics Purchase Intention: An Application of VBN Theory in Gen Z in Ho Chi Minh City: Online First: 25/06/2026 - Phan Ngọc Phương Anh,; Nguyễn Thị Thảo My,; Nguyễn Thúy Phương, (Journal of Technical Education Science, 2026)
This research investigates the impact of three core value orientations - biospheric, altruistic, and egoistic - on the purchase intentions of Generation Z consumers toward vegan cosmetics in Ho Chi Minh City. Grounded in the Value-Belief-Norm (VBN) framework, the study explores the psychological mechanisms driving green consumption. By analyzing 344 valid survey responses utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the results indicate that all three personal value dimensions show a positive correlation with the New Ecological Paradigm (NEP), with altruistic value exerting the strongest influence (β = 0.478; p < 0.05). Furthermore, the study examines the sequential mediating roles of awareness of consequences, ascription of responsibility, and personal norms. Within this structural model, personal norms emerge as the primary direct predictor of sustainable purchase intention (β = 0.767; p < 0.05). These findings provide empirical evidence for the theoretical framework of sustainable consumer behavior within the studied context and offer managerial implications for industry stakeholders in developing strategies to promote green consumption in the Vietnamese market.